A comparative analysis of commercial yield performance of Hevea clones in India - Joseph T; Chandy B; Lekshmi S; Viswanathan P K (Indian Journal of Natural Rubber Research, 1997)
The study analysed the comparative commercial yield performance and related aspects of 19 Hevea clones during the first ten years of tapping based on information on 467 fields, in the estate sector, with an area of 6881.24 ha. The analysis covered comparison of yield per ha, yield per tree, share of field coagulum (FC), tappable stand, tapping intensity, season-wise yield composition and a comparison of yield rates of India with those of Malaysia. The clone RRII 105 was found to be the highest yielding and reported relatively lower FC, higher tappable stand and lower tapping intensity. The RRIM clones other than RRIM 600 were low yielding showed diverse trends but among them PB 28/59, PB 260 and PB 217 were found to be high yielding ones. For the eight clones compared, the commercial yield in Malaysia were found to be higher than those in India.
Keywords: Clone evaluation; Commercial yield; Field coagulum; Natural rubber; Planting material; Tapping intensity